Investigation to design, fabricate, and integrate a mobile radiation monitoring system in ocean - Nguyen, Tien-Anh; Nguyen, Toan Van; Tran, Duc-Tan (Vietnam Journal of Science and Technology, 2023)
Ocean radiation monitoring and warning systems are essential in monitoring radioactive species’ contamination levels in an oceanic environment and predicting the radioactive materials propagation caused by nuclear incidents in a marine area. Since the Fukushima nuclear disaster, different types of mobile radiation monitoring devices have been investigated based on modern technologies in electronic – communication. Those types of equipment can directly measure the radioactive contamination in the ocean instead of the traditional laboratory method. This study presents a complete process of researching, designing, manufacturing, and integrating a mobile radiation monitoring system (MRMS) in the ocean. The integrated radiation sensor can both measure radiation dose rate and identify radioactive isotopes on a floating device. The measured data from the sensor is processed and displayed on the electronic block by developed software, or it can be transmitted directly to the mainland by one of three different communication devices. This prototype system is the first product in Vietnam in the development of the MRMS, which is highly promising in terms of performance, low cost, and maintenance.